Efektivitas Konseling Naratif untuk Meningkatkan Self-Efficacy Murid di SMP Negeri 2 Pattallassang Kabupaten Gowa - Nabila; Abdul Saman; Aswar; Maslina (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study was motivated by the presence of students who experienced difficulties in developing self-efficacy at SMP Negeri 2 Pattallassang. Low self-efficacy was indicated by students’ doubts about their abilities, lack of confidence in learning activities, and tendency to give up easily when facing academic tasks. This study aimed to determine the effectiveness of narrative counseling in improving students’ self-efficacy. The study employed a quantitative approach with a quasi-experimental design using a pretest-posttest non-equivalent control group design. The research sample consisted of 14 students selected through proportional random sampling and divided into experimental and control groups. Data were collected using a self-efficacy scale, observation, and interviews. The treatment was carried out through narrative counseling in the form of group counseling sessions. The results showed that narrative counseling was effective in improving students’ self-efficacy. After the treatment, students in the experimental group demonstrated increased self-confidence, courage in facing challenges, and persistence in completing tasks. Therefore, narrative counseling can be used as an alternative guidance and counseling service to improve students’ self-efficacy in schools